Yoga: An universal integrator and a potential tool for preventive health- An overview - et al., Mathew D (International Journal of Advanced Science and Technology, 2019)
Yoga is gaining popularity as an indigenous system of medicine across the globe. Yoga as bio-physical discipline can work in concurrence with any system of medicine to augment its efficacy in a positive way. Many studies have been published in the past 2 decades to identify the potential of yoga therapy in preventing and mitigating various systemic disorders. This review is aimed at identifying the mechanisms behind yoga in offering physiological homeostasis and thereby exploring its integrative potential with other systems of medicine. Further published literature will be explored to identify, if yoga can offer preventive health.